2014
DOI: 10.1128/jvi.02762-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Susceptibility of Transgenic Mice Overexpressing Deer Prion Protein to Bovine Spongiform Encephalopathy

Abstract: cSeveral transgenic mouse models have been developed which facilitate the transmission of chronic wasting disease (CWD) of cervids and allow prion strain discrimination. The present study was designed to assess the susceptibility of the prototypic mouse line, Tg(CerPrP)1536 ؉/؊ , to bovine spongiform encephalopathy (BSE) prions, which have the ability to overcome species barriers. Tg(CerPrP)1536 ؉/؊ mice challenged with red deer-adapted BSE resulted in 90% to 100% attack rates, and BSE from cattle failed to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Whereas, in both cases, primary transmissions may result in either all inoculated animals developing disease after a prolonged asymptomatic phase, or only a subpopulation of inoculated animals developing disease with variable incubation times, outcomes of secondary transmissions of the resulting prions reflect either adaptive-or nonadaptive amplification. The propagation of TME in TgD by NAPA contrasted the response of TgD to infection with prions from other species including sheep SSBP/1, mouse RML, and cattle BSE, which in all cases resulted in adapted deer prions that caused rapid, synchronous disease upon serial transmission to TgD (9,10,40). Our findings are therefore consistent with the notion that NAPA involves particular prion/PrP C interactions during transspecies transmissions.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas, in both cases, primary transmissions may result in either all inoculated animals developing disease after a prolonged asymptomatic phase, or only a subpopulation of inoculated animals developing disease with variable incubation times, outcomes of secondary transmissions of the resulting prions reflect either adaptive-or nonadaptive amplification. The propagation of TME in TgD by NAPA contrasted the response of TgD to infection with prions from other species including sheep SSBP/1, mouse RML, and cattle BSE, which in all cases resulted in adapted deer prions that caused rapid, synchronous disease upon serial transmission to TgD (9,10,40). Our findings are therefore consistent with the notion that NAPA involves particular prion/PrP C interactions during transspecies transmissions.…”
Section: Discussionsupporting
confidence: 81%
“…Out of 10 inocula that were negative in RIII mice, only one became positive when assayed in TgshpXI mice (see Supplementary Table 1a for details). Although TgshpXI mice were inoculated with only 20 ml of inoculum IC and RIII mice were inoculated with 20 ml IC plus 100 ml IP, previous studies in transgenic mice showed no difference between the two inoculation regimes (Beck et al, 2012;Vickery et al, 2014). While PrP d /PrP res is widely considered as the best surrogate marker for TSE infections, its relationship with actual infectivity is not always clear, either in qualitative or quantitative terms.…”
Section: Discussionmentioning
confidence: 97%
“…There is no data available on whether this species adaptation might alter the host range or virulence of the isolate, as has been reported previously for classical BSE [5255]. Previous reports on the transmission of L-BSE to sheep have only described the inoculation of animals that are ARQ/ARQ [40, 41] or ARQ/ARR [41].…”
Section: Discussionmentioning
confidence: 98%